PENGARUH REKLAMASI LAHAN TERHADAP SIFAT FISIKA DAN EROSI PADA LAHAN ALANG-ALANG - Aprisal Aprisal (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
A research about utilization of cylindrica biomass as an OM source was conducted to improve physical properties and to reduce soil erosion of degraded land and. The area of degraded land is quite large and the cylindrical biomass as a soil ameliorant is enough amount to use. The research was aimed to evaluate the effect of cylindrical biomass to improve properties and to reduce erosion of degraded Ultisol. Cylindrica biomass was treated as mulch as well as compost, sprayed with Round up, and removed from the land as farmers used to do. The field research was designed in Randomized Block Design (RBD). The result showed that cylindrical biomass was able to improve soil physical properties (BD, TP, infiltration rate) and to reduce erosion lower than the tolerated one. Keywords: land reclamation, erosion, tolerated erosion